1995
DOI: 10.3171/jns.1995.82.3.0413
|View full text |Cite
|
Sign up to set email alerts
|

Prospective double-blind placebo-controlled randomized trial on the use of ranitidine in preventing postoperative gastroduodenal complications in high-risk neurosurgical patients

Abstract: To determine the efficacy of ranitidine in preventing clinically acute overt gastroduodenal (GD) complications (bleeding and/or perforation) after neurosurgery, 101 patients with nontraumatic cerebral disease considered at high risk of developing postoperative GD complications were randomized in a standard double-blind manner to receive either ranitidine (50 mg every 6 hours) or placebo medication preoperatively. Postoperative serial GD endoscopy was used to document the occurrence of complications: an overt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…One review revealed an incidence of hemorrhagic ulcers of 12.5%, almost double to that in patients succumbing to non-neurological diseases [20]. Neurosurgical patients exhibit hypersecretion of pepsin and gastric acid [1,[21][22][23][24]. Severe TBI and Glasgow Coma Scale scores (GCS) of <9 have been associated with gastric acid hypersecretion and GI hemorrhage exceeding 17% [12, 15, and 25-32].…”
Section: Brain and Spinal Cord Injurymentioning
confidence: 99%
“…One review revealed an incidence of hemorrhagic ulcers of 12.5%, almost double to that in patients succumbing to non-neurological diseases [20]. Neurosurgical patients exhibit hypersecretion of pepsin and gastric acid [1,[21][22][23][24]. Severe TBI and Glasgow Coma Scale scores (GCS) of <9 have been associated with gastric acid hypersecretion and GI hemorrhage exceeding 17% [12, 15, and 25-32].…”
Section: Brain and Spinal Cord Injurymentioning
confidence: 99%
“…In the present study, a lower GCS score was associated with a higher risk of stress ulcer and gastrointestinal bleeding. Although gastric acid hypersecretion appears to play a key role in the pathogenesis of stress ulcer [8,16] , increased secretion of some reactive hormones, such as adrenaline, noradrenaline, adrenocorticotropic hormone or cortisol may also be involved [14,15] in this study because a majority of the patients with stress ulcer, 86.8%, had an increased level of cortisol within a day of the trauma, and the average cortisol level was inversely correlated to the GCS scores, suggesting that plasma cortisol is associated with the severity of the head injuries.…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies on neurosurgical patients and children undergoing cardiac surgery for congenital heart disease have shown that prophylactic use of gastric acid suppressants is recommended for high-risk patients, in order to avoid gastrointestinal lesions of greater severity. 12,13 Thus, stress ulcer prophylaxis during the postoperative period is not indicated routinely, but only for those with risk factors for clinically significant bleeding. [11][12][13][14] In this study, only a few patients (13%) did not receive prophylactic medication during the study period, thus suggesting that most anesthesiologists at this institution prefer to use these drugs routinely.…”
Section: -7mentioning
confidence: 99%
“…12,13 Thus, stress ulcer prophylaxis during the postoperative period is not indicated routinely, but only for those with risk factors for clinically significant bleeding. [11][12][13][14] In this study, only a few patients (13%) did not receive prophylactic medication during the study period, thus suggesting that most anesthesiologists at this institution prefer to use these drugs routinely. Although proton pump inhibitor and H2 receptor antagonists have been proven to be safe and well tolerated by most patients, it needs to be borne in mind that there are reports of adverse events in the literature.…”
Section: -7mentioning
confidence: 99%